Oxygen isotope composition of waters recorded in carbonates in strong clumped and oxygen isotopic disequilibrium - C. Thaler (Biogeosciences, 2020)
Paleoenvironmental reconstructions, which are mainly retrieved from oxygen isotope (δ18O) and clumped isotope (Δ47) compositions of carbonate minerals, are compromised when carbonate precipitation occurs in isotopic disequilibrium. To date, knowledge of these common isotopic disequilibria, known as vital effects in biogenic carbonates, remains limited, and the potential information recorded by δ18O and Δ47 offsets from isotopic equilibrium values is largely overlooked. Additionally, in carbonates formed in isotopic equilibrium, the use of the carbonate δ18O signature as a paleothermometer relies on our knowledge of the paleowaters' δ18O value, which is often assumed. Here, we report the largest Δ47 offsets observed to date (as much as −0.270 ‰), measured on microbial carbonates that are strongly linked to carbonate δ18O offsets (−25 ‰) from equilibrium. These offsets are likely both related to the microorganism metabolic activity and yield identical erroneous temperature reconstructions. Unexpectedly, we show that the δ18O value of the water in which carbonates precipitated, as well as the water–carbonate δ18O fractionation dependence on temperature at equilibrium, can be retrieved from these paired δ18O and Δ47 disequilibrium values measured in carbonates. The possibility to retrieve the δ18O value of paleowaters, sediments' interstitial waters or organisms' body water at the carbonate precipitation loci, even from carbonates formed in isotopic disequilibrium, opens long-awaited research avenues for both paleoenvironmental reconstructions and biomineralization studies.